Strikethrough! : typographic messages of protest - Munro, Silas; Coles, Stephen; Gaiter, Colette (San Francisco, CA : Letterform Archive, 2022)
"Strikethrough celebrates the use of letterforms to amplify and empower. In chapters exploring the many ways to voice dissent (RESIST!, VOTE!, STRIKE!, TEACH!, and LOVE!), this book charts a typographic chant of resistance across more than a century of protest graphics. With 180 objects ranging from nineteenth-century antislavery broadsides to the colorful affiches of the Paris 1968 uprising, from the revolutionary Black Panthers newspaper to the public awareness posters of the AIDS crisis, Strikethrough calls on us all to craft our own demands for social change."-- Provided by publisher.
Curatorial statement / Silas Munro -- NOW! Demanding Black liberation with typography / Colette Gaiter -- Type gives shape to voice / Stephen Coles -- RESIST! -- VOTE! -- STRIKE! -- TEACH! -- LOVE!.
Nimiösivulla myös: The official catalog for the 2022-2023 exhibition.
Includes bibliographical references and index.
englanti
Luett. SVe
KIRJA / BOK
Keywords: typografia; graafinen suunnittelu; visuaalinen viestintä; grafiikka; käyttögrafiikka; mainonta; kansitaide; julistetaide; poliittiset liikkeet; kansalaisoikeusliikkeet; aktivismi; näyttelyjulkaisut